Promoting children's sleep health: Intervention Mapping meets Health in All Policies - Belmon, Laura S.; Van Stralen, Maartje M.; Harmsen, Irene A.; Den Hertog, Karen E.; Ruiter, Robert A. C.; Chinapaw, Mai J. M.; Busch, Vincent (Frontiers in Public Health, 2022)
Background: To design a comprehensive approach to promote children’s sleep health in Amsterdam, The Netherlands, we combined Intervention Mapping (IM) with the Health in All Policies (HiAP) perspective. We aimed to create an approach that fits local infrastructures and policy domains across sectors. Methods: First, a needs assessment was conducted, including a systematic review, two concept mapping studies, and one cross-sectional sleep diary study (IM step 1). Subsequently, semi-structured interviews with stakeholders from policy, practice and science provided information on potential assets from all relevant social policy sectors to take into account in the program design (HiAP and IM step 1). Next, program outcomes and objectives were specified (IM step 2), with specific objectives for policy stakeholders (HiAP). This was followed by the program design (IM step 3), where potential program actions were adapted to local policy sectors and stakeholders (HiAP). Lastly, program production (IM step 4) focused on creating a multi-sector program (HiAP). An advisory panel guided the research team by providing tailored advice during all steps throughout the project. Results: A blueprint was created for program development to promote children’s sleep health, including a logic model of the problem, a logic model of change, an overview of the existing organizational structure of local policy and practice assets, and an overview of policy sectors, and related objectives and opportunities for promoting children’s sleep health across these policy sectors. Furthermore, the program production resulted in a policy brief for the local government. Conclusions: Combining IM and HiAP proved valuable for designing a blueprint for the development of an integrated multi-sector program to promote children’s sleep health. Health promotion professionals focusing on other (health) behaviors can use the blueprint to develop health promotion programs that fit the local public service infrastructures, and incorporate relevant policy sectors outside the public health domain.